How Poetry is Translated... - Shmiher, Taras (My University, 2018)
REVIEW: HOW POETRY IS TRANSLATED… James W. Underhill. Voice and Versification in Translating Poems. Ottawa: University of Ottawa Press, 2016. xiii, 333 p.
Keywords: poetry; translation; review; James W. Underhill